2010
DOI: 10.1105/tpc.110.074815
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into Maize Viviparous14, a Key Enzyme in the Biosynthesis of the Phytohormone Abscisic Acid

Abstract: The key regulatory step in the biosynthesis of abscisic acid (ABA), a hormone central to the regulation of several important processes in plants, is the oxidative cleavage of the 11,12 double bond of a 9-cis-epoxycarotenoid. The enzyme viviparous14 (VP14) performs this cleavage in maize (Zea mays), making it a target for the rational design of novel chemical agents and genetic modifications that improve plant behavior through the modulation of ABA levels. The structure of VP14, determined to 3.2-Å resolution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
165
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 57 publications
7
165
0
Order By: Relevance
“…S6). Due to the frame shift, the predicted mutant protein lacks highly conserved residues that are essential for the structure of a functional enzyme (Messing et al, 2010). Consistent with this conclusion, we note that the d10-2 mutation, a strong allele of rice D10, is due to a termination codon in the fifth exon that results in a 47-amino acid truncation from the C terminus (Arite et al, 2007).…”
Section: Conserved Function and Regulation Of Zmccd8supporting
confidence: 70%
See 2 more Smart Citations
“…S6). Due to the frame shift, the predicted mutant protein lacks highly conserved residues that are essential for the structure of a functional enzyme (Messing et al, 2010). Consistent with this conclusion, we note that the d10-2 mutation, a strong allele of rice D10, is due to a termination codon in the fifth exon that results in a 47-amino acid truncation from the C terminus (Arite et al, 2007).…”
Section: Conserved Function and Regulation Of Zmccd8supporting
confidence: 70%
“…S1), and the genetic map position of ZmCCD8 on the long arm of chromosome 3 (Supplemental Fig. S2) are well conserved in ZmCCD8 (Messing et al, 2010;Supplemental Fig. S3A).…”
Section: Identification Of a Single Ccd8 Gene In The Maize Genomementioning
confidence: 99%
See 1 more Smart Citation
“…] respectively, at 35°C, while seeds of the MIS2 mutant failed to germinate after 148 h of imbibition at 35°C, as did the wild-type DS seeds ( Figure 2B). Sequence alignment with VP14 from maize (Zea mays), which shares 51% amino sequence identity with NCED4 and for which a tertiary structure has been published (Messing et al, 2010), showed that both the STOP1 and MIS1 mutations occurred near a His residue (His-412) that is involved in binding an iron atom that is essential to the active site of the enzyme, while the MIS2 mutation is not near the active site (see Supplemental Figures 4A and 4B online). The ABA content of mature MIS1 mutant seeds was about half that of the wild-type DS seeds, while the ABA content of the STOP1 mutant seeds was reduced by ;20% (Table 1).…”
Section: Gain or Loss Of Function Of Nced4 Can Mediate Lettuce Seed Tmentioning
confidence: 99%
“…Polymorphisms identified in SxMAX4E may be responsible for the inability of this allele to show full MAX4 activity. These include changes in residues highly conserved among MAX4 orthologs, such as R217S, but no specific function has been proposed for this residue (Messing et al, 2010;Delaux et al, 2012).…”
Section: Future Prospects For Breedingmentioning
confidence: 99%